El Índice de Sociedad Sostenible (SSI) en América: análisis desde una perspectiva de Biplot dinámico - De La Hoz Maestre, Javier; Montes Escobar, Karime; Salas Macías, Carlos (El Colegio de México A.C., 2021)
This study presents a dynamic Biplot analysis of the Sustainable Society Index applied to the American continent. The main results when analyzing the trajectories of the variables in general are short and tend to improve. Two groups were observed: the first joins countries well positioned against the variables “basic needs” and “personal and social development” (North America), and the second puts together countries with irregular behavior trajectories, with little stability and with a tendency to fall in the last periods in analysis (Central, South America and the Caribbean). The Dynamic Biplot method proves to be a new approach to three-way data processing and provides results that are easy to represent and interpret.